Comparing the Color of Fear and Evolution of a Group : A Pilot Study - Torres Rivera, Edil
Compara dos películas: El color del miedo y Evolución de un grupo usando el Multicultural awareness knwloedge and skills survey y el counselor skills and personal development rating from.